Treatment of Long Bone Fractures with Locking Kuntscher Nail in Dogs - Karahalli, A; Sarierler, M (Journal of the Hellenic Veterinary Medical Society, 2025)
In this study, it was aimed to evaluate the treatment of long bone fractures with ''Locking Küntscher'' nails in dogs under the light of clinical and radiographic findings. The study material consisted of 16 dogs in different races, ages, and genders with the diagnosis of diaphyseal fracture in femur or tibia. In the fractures reached with standard surgery technique, the operations were performed using Locking Küntscher nails and locking cortical screws in the sizes determined by using the x-ray results in the preoperative period. The cases underwent radiographic examinations every week during post-operative 4 weeks and lameness scores were obtained. In one case, after the postoperative 7th day, callus exuberant was observed and it was determined that the lameness score was at level 4. In one case, during the operation, the nail was determined to be broken in medullada after passing the fracture line, and the score of lameness level on the postoperative 7th day was determined as 1. It was determined that the cortical screws applied in one case had missed the the distal holes and the lameness score was determined as 1. in another case, the nail was broken from its distal part in postoperative 15th day, and the lameness score was determined as 1. As a result; under the light of clinical and radiographical findings; it was concluded that Locking Küntscher nails may be preferred in long bone fractures of dogs because of its advantages over current treatment methods with its high success and low complication rates, especially because of the fact that it completely removes pin migration and allows early use of the extremity.